Complementary Progressive Muscle Relaxation Therapy in Elderly People with Degenerative Diseases: Literature Review - Bachtiar Safarudin; Raden Andi Rosa; Amelia Kartika Sari; Nurfadilah Arman; Diazty; Priska Cahya Ningtyas; Refita Yuniar; Annisa Natasya Putri; Hanif Daffa Fauzan Rizki; Mohammad Ananta Pratama; Aji M Ansyar (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Older adults often experience various degenerative diseases such as hypertension, diabetes mellitus, and osteoarthritis, which impact physical function and quality of life. Non-pharmacological nursing interventions such as Progressive Muscle Relaxation (PMR) are increasingly being used to improve physical and psychological well-being. This study aims to systematically review the effectiveness of PMR therapy as a complementary nursing intervention. Method: A systematic literature review was conducted using the PRISMA approach. Articles were obtained through searches on Google Scholar, PubMed, ScienceDirect, and Publish or Perish using the keywords “progressive muscle relaxation,” “elderly,” and “degenerative diseases.” Inclusion criteria included Indonesian or English journal articles published in the last five years, with full text and clear methodology. A total of 15 articles met the criteria and were analyzed. Result: Most studies used a quasi-experimental or pre-posttest design with a sample size of between 20 and 100 elderly respondents. The results of the study showed that PMR was effective in reducing blood pressure, muscle tension, pain, and anxiety. Conclusion: Progressive Muscle Relaxation is an effective, simple, and low-cost non-pharmacological nursing intervention to improve the physical and psychological health of elderly people with degenerative diseases.